MANAJEMEN HUMAS DALAM MENINGKATKAN CITRA SEKOLAH DASAR ISLAM SURYA BUANA DINOYO KOTA MALANG - Karnoto, Ahmad (Program Studi Manajemen Pendidikan Islam Fakultas Ilmu Tarbiyah dan Keguruan UIN Maulana Malik Ibrahim Malang, 2024)
Public relations is a continuous effort to increase understanding between an institution and the community. Apart from that, public relations tries to make the image of the madrasah be seen as good by the public, or society. This is intended so that madrasas can survive and become more creative and useful for others. Progress in various fields has allowed public relations to emerge in its modern form. In the modern era, managing educational institutions requires combining promotional and marketing strategies with social interests. In research entitled